A retrospective cohort study: vaccination status and safety analysis of SARS-CoV-2 vaccine in patients with Wilson's disease - Hui Han; Dan Zhao; Xinru Fang; Wenming Yang; Mengli Wang; Qianzhuo Liu; Luyao Wang; Zhihui Ji; Juan Zhang; Zhifeng Hou; Lei Hua; Yu Wang; et al. (Taylor & Francis Group, 2023)
ABSTRACTBackground Wilson's disease (WD) is a rare hepatic and neurological disorder, which can dramatically worsen by traumatic injuries, surgeries, and infections. No studies have reported safety data of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination in WD patients. We aimed to investigate the SARS-CoV-2 vaccination status and post-vaccination adverse events in WD patients.Methods This is a multicenter, retrospective, observational study. We investigated the vaccination rates, the type of vaccine, subjective reasons for non-vaccination, and the adverse events following vaccination. Logistic regression analysis was used to assess the correlation between vaccination status and increased Unified Wilson's Disease Rating Scale (UWDRS) scores.Results A total of 554 WD patients with a mean (SD) age of 25.3 (10.85) years were included in this study, of whom 336 (60.6%) were males and 218 (39.4%) were females. 368 (66.4%) patients received at least one dose of the SARS-CoV-2 vaccine.186 (33.6%) patients were unvaccinated. Logistic regression analysis showed that vaccination against SARS-CoV-2 was not significantly associated with increased UWDRS scores. The safety analysis demonstrated that 21.2% had post-vaccination adverse events.Conclusions In this study, vaccination against SARS-CoV-2 was safe in WD patients, providing evidence for the safety of vaccination in WD patients.